Pengaruh Struktur Kepemilikan, Kebijakan Dividen, dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Perbankan BUMN Dan BUMD Yang Terdaftar Di Bursa Efek Indonesia - Ahmad Syawal; Masdar Mas'ud; Muh. Arif (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
Abstract This study aims to examine the impact of ownership structure, dividend policy, and firm size on firm value. The sample in this study consisted of six state-owned and regionally-owned banking companies listed on the Indonesia Stock Exchange for the 2020-2024 period. This study used a quantitative approach with time series data. The data analysis technique used panel data regression with the help of E-Views. The results show that (1) ownership structure has a negative and significant effect on firm value, meaning that the higher the proportion of institutional ownership, particularly ownership by the central and regional governments, the lower the firm value. (2) Dividend policy does not have a significant effect on firm value, meaning that the amount of dividends distributed by state-owned and regionally-owned banking companies is not a major factor influencing investors' perceptions of firm value. (3) Company size has a positive and significant effect on company value, meaning that the larger the company, the higher the company value, as reflected in investor perceptions. (4) Ownership structure, dividend policy, and company size simultaneously have a significant effect on company value. Keywords: Ownership Structure, Dividend Policy, Company Size, Company Value